(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article systematically analyzes the scientific activities and contributions of foreign scholars who first conducted archaeological research in Arab countries, as well as the national research efforts undertaken by Arab scholars and the operations of scientific research centers in this field. It provides significant information regarding the establishment process of the “Arab Archaeologists Union,” its historical importance, and its current activities. Additionally, the scholarly works of Arab researchers who have investigated the history of Turan are thoroughly examined, their methodological approaches are identified, and the distinctive features of these studies are elucidated